Self-Management of Kidney Transplant Recipients Research: A Comprehensive Bibliometric Analysis - Lou J; Hu Z; Yuan M; Luo R; Zhang T; Ye Q; Zhou X; Feng B (Journal of Multidisciplinary Healthcare)
Jiaao Lou,1,2,* Zhengbin Hu,1,* Menglin Yuan,1 Rui Luo,1 Tao Zhang,1 Qifa Ye,1,3 Xin Zhou,1 Bilong Feng2 1Institute of Hepatobiliary Diseases of Wuhan University, Transplant Center of Wuhan University, National Quality Control Center for Donated Organ Procurement, Hubei Key Laboratory of Medical Technology on Transplantation, Hubei Clinical Research Center for Natural Polymer Biological Liver, Hubei Engineering Center of Natural Polymer-Based Medical Materials, Zhongnan Hospital of Wuhan University, Wuhan, Hubei Province, 430071, People’s Republic of China; 2Department of Nursing, Zhongnan Hospital, Wuhan University, Wuhan, Hubei Province, People’s Republic of China; 3Research Center of National Health Ministry on Transplantation Medicine Engineering and Technology, The 3rd Xiangya Hospital of Central South University, Changsha, Hunnan Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xin Zhou, Institute of Hepatobiliary Diseases of Wuhan University, Transplant Center of Wuhan University, National Quality Control Center for Donated Organ Procurement, Hubei Key Laboratory of Medical Technology on Transplantation, Hubei Clinical Research Center for Natural Polymer Biological Liver, Hubei Engineering Center of Natural Polymer-based Medical Materials, Zhongnan Hospital of Wuhan University, Wuhan, Hubei Province, 430071, People’s Republic of China, Tel +86 027-67813423, Email 13545133367@163.com Bilong Feng, Department of Nursing, Zhongnan Hospital, Wuhan University, #169, East Lake Road, Wuchang District, Wuhan, Hubei Province, 430071, People’s Republic of China, Tel +86 027-67812888, Email fbl1019@126.comObjective: This study analyzes research trends in self-management among kidney transplant recipients to inform future directions.Methods: Bibliometric analysis was performed on 444 English articles related to self-management of kidney transplant recipients in the Core Collection of Web of Science and Scopus databases using COOC 12.8, R software, Microsoft Excel 2019, VOSviewer, and CiteSpace, with a focus on citation ranking, publication year, journal, country, organization, author, impact factor, and keywords.Results: Four hundred and forty-four English articles revealed the United States as the leading publisher on kidney transplant recipient self-management. Norway’s University of Oslo was the most productive institution, with Mirjam Tielen as the most prolific author and SCHÄFER-KELLER as the most influential. Belgium’s research was most cited. Emerging hotspots included medication adherence, quality of life, psychological aspects, telemedicine, and health literacy in self-management research.Conclusion: This study has identified the most influential articles concerning the self-management of kidney transplant recipients, documented the pivotal journals in the field, and noted the most prolific countries, organizations, and authors contributing to the literature, as well as highlighted upcoming research trends. Going forward, the research in kidney transplant recipient self-management should explore the full potential of interdisciplinary integration, particularly by incorporating telemedicine into self-management education. Future efforts should also be directed towards refining the existing post-transplant follow-up management systems and enhancing lifelong care for kidney transplant recipients. Concurrently, there is a need to improve health literacy and self-management capabilities among these patients, with the ultimate goal of improving their prognosis.Keywords: self-management, kidney transplant, recipients, bibliometric analysis, visual analysis